2022
DOI: 10.1002/srin.202100773
|View full text |Cite
|
Sign up to set email alerts
|

Transient Evolution of Nonmetallic Inclusions in a Si–Mn‐Killed Stainless Steel with Cerium Addition

Abstract: Laboratory experiments are performed to study the transient evolution of inclusions in Si–Mn‐killed stainless steels with additions of 40, 100, and 400 ppm cerium. With the increase of the cerium content in the molten steel, the evolution path of inclusions is Al2O3–SiO2–MnO–CaO → Ce2O3–Al2O3–SiO2–MnO–CaO → Ce2O3 → Ce2O3–CeS. The addition of 40 ppm cerium gradually increases the Ce2O3 content in liquid oxide inclusions. After the addition of 100 ppm cerium, inclusions first evolve to Ce2O3–Al2O3–SiO2–CaO–CeS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Specifically, the balance between the Ce 2 O 3 -containing refining slag and the molten steel-containing aluminum will lead to a small amount of cerium being dissolved into the molten steel. This rare earth element can perform a vital role in purifying, modifying, and micro-alloying steels [138], modifying the inclusions [139][140][141][142], refining the solidification structure [143], and improving the performance [144][145][146] of RE steels. The effects of rare earth elements on the modification of inclusions have been widely studied, both in lab experiments and within industrial scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the balance between the Ce 2 O 3 -containing refining slag and the molten steel-containing aluminum will lead to a small amount of cerium being dissolved into the molten steel. This rare earth element can perform a vital role in purifying, modifying, and micro-alloying steels [138], modifying the inclusions [139][140][141][142], refining the solidification structure [143], and improving the performance [144][145][146] of RE steels. The effects of rare earth elements on the modification of inclusions have been widely studied, both in lab experiments and within industrial scale production.…”
Section: Introductionmentioning
confidence: 99%
“…On changing microstructure, inclusions could fine grains by offering nucleation site for ferrite, [4][5][6][7] which was helpful to the properties. And on modifying inclusions, inclusions could make harmful inclusions form beneficial inclusions, 4,8 such as Ca-treat in Al-killed steel. 9,10 There were two important aspects for inclusions, formation mechanism of inclusions and effect of refining grains.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [13] investigated the effect of cerium (Ce) on the morphology of Al 2 O 3 inclusions and determined that, after adding Ce, inclusions changed from a morphology of long strip and sharp angle to spherical and spindle surface. Zhang et al [14] demonstrated the evolution path of inclusions with an increased Ce content in Si-Mn-killed steel, from Al 2 O 3 -SiO 2 -MnO-CaO to Ce 2 O 3 -Al 2 O 3 -SiO 2 -MnO-CaO, Ce 2 O 3 , and Ce 2 O 3 -CeS. Huang et al [15] reported the inclusion evolution process when the Ce content increased from 0-0.03% in H13 steel, as changed from MgO•Al 2 O 3 to CeAlO 3 , Ce-O, and Ce-O-S…”
Section: Introductionmentioning
confidence: 99%